2022
DOI: 10.1080/13880209.2022.2098346
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effects of extracts obtained from plants of the Oleaceae family: bio-guided isolation and molecular docking of new secoiridoids from Jasminum humile

Abstract: Context Traditionally, Oleaceae plants are used to treat many diseases, such as rheumatism, hypercholesterolaemia, or ulcers. Objectives To investigate the cytotoxic potential of Jasminum humile L., Jasminum grandiflorum L., and Olea europaea L. (Oleaceae) extracts against selected human cancer cells lines, followed by a phytochemical investigation of the most potent one. Mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…The valid performance was confirmed in each case by obtaining low root mean square deviation (RMSD) values (0.90 and 0.08 Å, respectively). Besides, the same binding mode was observed by overlaying both the native (green) and redocked (red) co-crystallized ligand in each binding pocket [ 48 ], Figure 3 .…”
Section: Methodsmentioning
confidence: 66%
“…The valid performance was confirmed in each case by obtaining low root mean square deviation (RMSD) values (0.90 and 0.08 Å, respectively). Besides, the same binding mode was observed by overlaying both the native (green) and redocked (red) co-crystallized ligand in each binding pocket [ 48 ], Figure 3 .…”
Section: Methodsmentioning
confidence: 66%
“…They can be used as a ligand for Caspase-3 receptors in breast cancer cells ( Mutazah et al, 2020 ). Molecular docking studies on Jasminum humile by using two compounds, namely 1-methoxyjasmigenin and 1-methyl-9-aldojasmigenin, showed that these compounds could be used as anticancer drugs targeting Mcl-1 ( Mansour et al, 2022 ). Molecular docking studies on Raphia taedigera seed oil possess compounds like 3-Methoxy-2,3-dimethylundec-1-ene, which can be used as a target for VEGFR-2 binding and can be used as an anticancer agent ( Umar et al, 2021 ).…”
Section: Molecular Docking Studies For Anticancer Compounds From Diff...mentioning
confidence: 99%
“…Targeting specific components of the tumor extracellular matrix to normalize the tumor microenvironment has recently been proposed as a means to decompress tumor blood vessels, promote vascular perfusion, and hence improve drug delivery and cancer therapy efficacy [115] , [116] , [117] , [118] . As a result, the researchers set out to discover safe and well-tolerated pharmacological compounds that could modify the microenvironment of solid tumors [119] , [120] , [121] , [122] , [123] .…”
Section: Pharmacological Effects Of Pfdmentioning
confidence: 99%